DAMPAK KENAIKAN CUKAI ROKOK TERHADAP LABA PT. GUDANG GARAM TBK UNTUK TAHUN 2020, 2021, DAN 2022 - Ummaroh (Journal Accounting International Mount Hope, 2024)
The aim of this study is to find out the impact of the increase in cigarette taxes specifically on profits of PT. The authors used the financial reports for the periods 2020, 2021, and 2022 and the Finance Minister's regulations on the increase in cigarette taxes for the years 2020, 2021 and 2022 as the source of research data. The research method used by the author is a qualitative approach that is by observing the financial report of PT. Salt Warehouse Tbk and the large data of the increase in cigarette tax contained in the annex to the Regulations of the Ministry of Finance. The results of the research show that the increase in the tax rate on cigarettes has a significant impact on the profit value of the Salt Warehouse. The average decline in profits reached 36% over three years